Probiotics for preventing ventilator-associated pneumonia: a systematic review and meta-analysis of high-quality randomized controlled trials. - Jie Wang; Kai-xiong Liu; Felinda Ariani; Li-Li Tao; Jing Zhang; Jie-Ming Qu (PLoS ONE, 2013)
Background Ventilator-associated pneumonia (VAP) is considered to be a worldwide issue along with the development of supportive ventilation. The preventing strategy is of great importance for its poor prognostic and difficulties in treatment. Probiotics have been advocated as one of the possible preventive measures. We conducted a systematic review and meta-analysis to explore the potential benefits of probiotics. Methods The databases, Web of science, PubMed, Ovid and Cochrane lib were searched for randomized controlled trials (RCTs) publications that compared the effectiveness of probiotics with placebo in the prevention of VAP. The incidence of VAP was considered as the primary endpoint, mortality, length of stay in intensive care units (ICUs), etiology of the infections were considered as secondary endpoints. Results A total of 844 patients from 5 trials were subjected to meta-analysis. Probiotics did not significantly decrease the incidence of VAP (RR 0.94, 95%CI 0.85-1.04, p=0.22), however, the administration of probiotics reduced the risk of VAP caused by Pseudomonas aeruginosa (P. aeruginosa) (RR 0.30, 95%CI 0.11-0.91, P=0.03). It failed to affect any other endpoints. Conclusion Probiotic prophylaxis of ventilator-associated pneumonia remained inconclusive and it failed to improve the prognosis of general mechanically ventilated patients. It was noteworthy that infections caused by P. aeruginosa was reduced by administration of probiotics. In further, it is recommended that advanced studies should exploit transformation in pathogenic microorganisms owing to administration of probiotics as well as the specific population.